PENCIPTAAN FILM DOKUMENTER œSOTUNG MAGO MENGGUNAKAN GAYA EKSPOSITORY - Surya Darma; Sri Wahyuni; Haga Putra Arza Polem (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2023)
Sotung Mago is a Batak language which means don't disappear. The film Sotung Mago explains anxiety to the younger generation of children who do not know and understand the meaning of art, especially in this case the Toba Batak. According to Dennis Huisman art can be conceptualized as an activity imitating nature, an activity playing around with art forms. Art can be equated with work methods or carpentry methods and techniques. Meanwhile, culture contains the whole understanding of values, norms, knowledge and all social, religious and other structures. Art and culture are usually interrelated or related which are inherited by the community, especially in this case the Batak. However, not a few people have ignored the artistic heritage in the Toba Batak so that the current generation doesn't know about it. The purpose of this research is to explore the creation of the documentary film œSotung Mago using expository style and to visualize several Toba Batak arts through documentary films. The method used refers to the stages of creative creation, namely the Preparation Stage, Incubation Stage, Illumination Stage (inspiration stage), and finally the Verification stage (proof or testing stage). The results of the Creation of the Documentary Film